On Neyman-Pearson Principle in Multiple Hypotheses Testing - Haroutunian, Evgueni A.; Hakobyan, Parandzem M. (Mathematical Problems of Computer Science, 2021)
The aim of this paper is to newly generalize the classical Neyman-Pearson Lemma to the case of more than two simple hypotheses.